2006
DOI: 10.1007/s00213-006-0366-7
|View full text |Cite
|
Sign up to set email alerts
|

Persistent dysfunctional frontal lobe activation in former smokers

Abstract: For the first time, evidence is provided that dysfunctional activation of frontal lobe networks in smokers is also present in long term abstainers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 69 publications
9
60
0
1
Order By: Relevance
“…Also implicating cholinergic factors in P300, Neuhaus et al (2006) reported reduced P300s in both current smokers (for about 20 years) and former smokers (about 12 years abstinence), relative to never smokers. This may point to a relatively strong disposition to indulge in smoking behavior in low-P300 individuals, perhaps to compensate low natural cholinergic transmission; or chronic smoking alters the cholinergic system and thereby P300 in an irreversible manner, perhaps through receptor desensitization.…”
Section: 'Attention' and Memory Updating: P300mentioning
confidence: 88%
See 1 more Smart Citation
“…Also implicating cholinergic factors in P300, Neuhaus et al (2006) reported reduced P300s in both current smokers (for about 20 years) and former smokers (about 12 years abstinence), relative to never smokers. This may point to a relatively strong disposition to indulge in smoking behavior in low-P300 individuals, perhaps to compensate low natural cholinergic transmission; or chronic smoking alters the cholinergic system and thereby P300 in an irreversible manner, perhaps through receptor desensitization.…”
Section: 'Attention' and Memory Updating: P300mentioning
confidence: 88%
“…Cholinergic transmission is an important determinant of P300 amplitude, a reflection of attention allocation predictive of subsequent memory, and probably based in a posterior cortical network, including temporal and parietal areas, as well as well possibly posterior cingulate cortex (Neuhaus et al, 2006). ACh further augments MMN (temporally and frontally) as well as P50 suppression, although the latter effect is believed to be indirect (Adler et al, 2004).…”
Section: Wrapping Up Neurotransmission Drugs and Cortical Processingmentioning
confidence: 99%
“…Neuhaus et al, (2006) revealed persistent fronto-striatal dysfunction in former smokers despite a mean of 11 years of abstinence from cigarette smoking. In addition to other functional differences, they reported decreased cortical activation in orbitofrontal and left dorsolateral prefrontal regions amongst previous smokers when completing an auditory oddball task.…”
Section: Executive Function Treatment Recovery In Nicotine Dependencementioning
confidence: 98%
“…However, research has yielded mixed results. Impairment of response inhibition among smokers continues across 3 months of abstinence [28] and hypoactivation in the frontal lobes has been observed among long term abstainers [29] suggesting executive deficits may persist among smokers. In contrast, other research maintains executive dysfunction associated with tobacco addiction may be more malleable.…”
Section: Journal Of Addiction Research and Therapymentioning
confidence: 99%
“…Tobacco dependence was measured via the Fagerstrom Test of Nicotine Dependence (FTND) [40]. Most studies of executive deficits and nicotine addiction have employed cross sectional research designs [12,29,30] or measured executive abilities initially and related them to subsequent treatment attrition or outcomes [31,32]. This study was relatively unique in that it assessed executive abilities in the same participants prior to treatment and approximately one and a half months after the initiation of treatment.…”
Section: Journal Of Addiction Research and Therapymentioning
confidence: 99%